Perfil del director de comunicación: habilidades y competencias en los gobiernos locales - Elizalde Chamba, Anthony Joel (Machala : Universidad Técnica de Machala, 2025)
This research analyzes the professional profile of the Director of Communication (DirCom) in the Decentralized Autonomous Governments (GADs) of El Oro, Ecuador, with the aim of identifying their functions, competencies, and training needs. Based on interviews conducted with 13 DirComs, four key dimensions were evaluated: strategic role, leadership, digital competencies, and professional development. The findings show that while DirComs participate in institutional planning and lead communication strategies, they face limitations in autonomy, resources, and continuous training. A predominantly participative leadership style is evident, along with widespread use of digital tools, yet gaps remain in metric analysis and public sector regulations. Recommendations are proposed to strengthen the DirCom’s professional profile within the context of local public administration.
Esta investigación analiza el perfil del Director de Comunicación (DirCom) en los Gobiernos Autónomos Descentralizados (GAD) cantonales de El Oro, Ecuador, con el objetivo de identificar sus funciones, competencias y necesidades de formación. A partir de entrevistas aplicadas a 13 DirCom, se evaluaron cuatro dimensiones clave: rol estratégico, liderazgo, competencias digitales y formación profesional. Los resultados muestran que, aunque los DirCom participan en la planificación institucional y lideran estrategias comunicacionales, enfrentan limitaciones en autonomía, recursos y formación continua. Se evidencia un liderazgo mayoritariamente participativo, un uso extendido de herramientas digitales y vacíos en el análisis de métricas y normativas públicas. Se proponen recomendaciones para fortalecer el perfil profesional del DirCom en el contexto de la gestión pública local.
Keywords: COMUNICACIÓN INSTITUCIONAL; DIRECTOR DE COMUNICACIÓN; COMUNICACIÓN ESTRATÉGICA; COMPETENCIAS PROFESIONALES